Understanding mobile augmented reality adoption in a consumer context - Paulo, M. M. (2018)
Purpose The purpose of this paper is to further our knowledge of what influences users to adopt mobile augmented reality in tourism (MART). A conceptual model is proposed, combining the extension of Unified Theory of Acceptance and Usage of Technology (UTAUT2) with task technology fit (TTF), to explain behavioural intention and user behaviour of MART adopters. Design/methodology/approach A questionnaire was completed by a sample of 335 respondents in Portugal. Both UTAUT2 and TTF were combined into a new model from which several hypotheses were drawn based upon the literature. Findings The results have shown that the model explains 72 per cent of the variance in behaviour intention to use MART and 45 per cent of the variance in user behaviour. Originality/value MART is becoming increasingly known to travellers as it provides the user diverse and useful information with a real relationship with the world. By studying behaviour and what influences consumers to use MART, this study aims to advance the research into new technologies in tourism.